Anaphase lag as the most likely mechanism for monosomy X in direct cytotrophoblasts but not in mesenchymal core cells from the same villi. Issue 12 (December 1990) - Qumsiyeh, M B; Tharapel, A T; Shulman, L P; Simpson, J L; Elias, S
Abstract : A 36 year old white female was referred for chorionic villus sampling for advanced maternal age. Direct (cytotrophoblast) preparations of chorionic villi were 45, X, but cultured mesenchymal core cells from the same villi were 46, XX. Study of embryonic and extraembryonic tissues showed the aneuploidy to be limited to cytotrophoblasts from specific placental sites. In aggregate, the cytogenetic findings can best be explained by anaphase lag during development of the cytotrophoblast, suggesting that this cytological mechanism and not non-disjunction is responsible for the common occurrence of monosomy X in villi.